1996
DOI: 10.1210/jcem.81.1.8550770
|View full text |Cite
|
Sign up to set email alerts
|

Counterproductive effects of sodium bicarbonate in diabetic ketoacidosis.

Abstract: Although a growing body of evidence supports that alkali therapy in diabetic ketoacidosis (DKA) might be counterproductive, our knowledge about the consequences of this treatment on ketone metabolism is limited. Consequently, we performed clinical and animal studies to further examine this topic. The clinical studies assessed seven patients with DKA treated with continuous insulin infusion at a low dosage. Three of them also received sodium bicarbonate (NaHCO3), whereas the remaining four acted as controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…In some cases, administration of sodium bicarbonate may produce deleterious effects, which include increased ketone body formation, decreased ketone body metabolism, and cerebral edema. [5][6][7][8][9] Our study also attempted to determine the correlation and precision between venous pH and arterial pH values. Previous studies have shown an excellent correlation of arterial and venous pH values in the laboratory and various clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, administration of sodium bicarbonate may produce deleterious effects, which include increased ketone body formation, decreased ketone body metabolism, and cerebral edema. [5][6][7][8][9] Our study also attempted to determine the correlation and precision between venous pH and arterial pH values. Previous studies have shown an excellent correlation of arterial and venous pH values in the laboratory and various clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…1 Sodium bicarbonate therapy has not been proven to be beneficial to DKA patients with a pH equal to or greater than 6.9. [5][6][7][8][9] An increased anion gap is a predictor of the presence of metabolic acidosis, and the related degree of acidosis can be estimated by the size of the anion gap. The acidemia of DKA can be attenuated by the respiratory alkalosis commonly associated with DKA, IV fluid administration, and insulin administration to the patient.…”
mentioning
confidence: 99%
“…Quanto maior o acúmulo de ácidos orgânicos, maior a queda no bicarbonato sérico e, consequentemente, mais elevado é o AG. [10][11][12][13][14] [d] Portanto, a magnitude da elevação do AG reflete a magnitude do acúmulo de ácidos orgãnicos. Com o tratamento da doença de base e a reversão das condições metabólicas responsáveis pela produção excessiva destes ácidos orgânicos, o acetato e o lactato são rapidamente convertidos em bicarbonato (sendo, por isso, considerados precursores de bicarbonato ou "bicarbonato em potencial").…”
Section: Tipos De Acidose Metabólica: Implicações Terapêuticasunclassified
“…Para a reposição de bicarbonato, o ideal é a monitoração pela hemogasometria, calculada pela fórmula [Bicarbonato (mEq) = Peso(kg)x0,4x(24 -bicarbonato paciente) x 0,5], em que o fator 0,5 indica metade da dose a ser infundida lentamente pela via intravenosa no período de seis horas (BRUYETTE, 1997). Estudos em humanos com CAD demonstraram que a administração de bicarbonato não traz benefícios em pacientes com pH sanguíneo entre 6,9 e 7,1 (VIALLON et al, 1999), além de levar ao aumento da cetogênese hepática (OKUDA et al, 1996). De acordo com BARONE et al (2007), existem evidências de que a terapia com bicarbonato pode aumentar a síntese de corpos cetônicos, contrapondo-se, assim, aos efeitos da insulina.…”
Section: Tratamento E Prognósticounclassified